Characteristics of developed flexible polyurethane foams reinforced with coconut coir fibres and recycled tyres - Chan, Wen Shan (2012)
Flexible Polyurethane (PU) foam is generally used in seat cushions of automotive seating for comfort and supporting the occupants. However, due to the demand for more comfortable compartment; seat cushions are now designed for better riding comfort and acoustic absorption which linked to the damping of foam. Incorporated treated coir fibres (F) and tyre particles (P) into polymeric material had improved the damping and strength of the material. In this research, flexible PU foams were reinforced with two fillers for the purpose of higher damping property and improve the mechanical strength. Five samples with 2.5wt% of filler loading were developed. The damping of samples was measured on sound absorption and vibration transmissibility test that generated at 1mm, 1.5mm, 0.1g, and 0.15g base excitation while their mechanical properties were examined through compression, tear resistance, and compression set. The morphology of samples was also observed by SEM in this research. The results showed that the foam composites produced have smaller cell size, in which the smallest was 840µm compared to 1290µm obtained in pure PU foam. The mechanical properties revealed that the strength of flexible PU foam increased with added treated coir fibres and recycled tyres. The best properties were shown in PU+2.5wt%(50F50P) which increased by 10.78% on the compressive modulus, 9.33% on the compressive strength, 14.49% on the static energy absorption, and 3.76% on the tear strength compared to pure PU foam. The sound absorption and vibration damping of the developed foams showed that more energy were absorbed and dissipated by these foams after fillers added. The PU+2.5wt%(80P20F) and PU+2.5wt%F presented an excellent sound absorption characteristics at 20mm and 40mm thickness, respectively, whereas PU+2.5wt%P, PU+2.5wt%(80P20F), and PU+2.5wt%(80F20P) showed higher vibration damping from the transmissibility test.